2017
DOI: 10.1111/nph.14469
|View full text |Cite
|
Sign up to set email alerts
|

In situ temperature response of photosynthesis of 42 tree and liana species in the canopy of two Panamanian lowland tropical forests with contrasting rainfall regimes

Abstract: Tropical forests contribute significantly to the global carbon cycle, but little is known about the temperature response of photosynthetic carbon uptake in tropical species, and how this varies within and across forests. We determined in situ photosynthetic temperature-response curves for upper canopy leaves of 42 tree and liana species from two tropical forests in Panama with contrasting rainfall regimes. On the basis of seedling studies, we hypothesized that species with high photosynthetic capacity - light-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
154
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(165 citation statements)
references
References 79 publications
11
154
0
Order By: Relevance
“…While in seedlings the optimum and maximum temperature for net photosynthesis is higher in early‐ than in late‐successional species (Slot et al., ), in leaves of canopy trees this difference in temperature‐response traits disappears (Slot & Winter, ). This change probably reflects adaptation to the common ontogenetic trajectories of early‐ and late‐successional canopy trees; while early‐successional species tend to germinate in open areas and maintain high‐light exposure—and thus higher tissue temperatures—throughout their development, late‐successional canopy species start out as seedlings in the shaded understorey—buffered against high leaf temperatures—but experience high light and high temperature conditions as adults in the canopy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While in seedlings the optimum and maximum temperature for net photosynthesis is higher in early‐ than in late‐successional species (Slot et al., ), in leaves of canopy trees this difference in temperature‐response traits disappears (Slot & Winter, ). This change probably reflects adaptation to the common ontogenetic trajectories of early‐ and late‐successional canopy trees; while early‐successional species tend to germinate in open areas and maintain high‐light exposure—and thus higher tissue temperatures—throughout their development, late‐successional canopy species start out as seedlings in the shaded understorey—buffered against high leaf temperatures—but experience high light and high temperature conditions as adults in the canopy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…During the calculation, we assumed that (1) ambient temperature and vapour pressure deficit for A sat measurements are equal to long‐term average values at 10:00 AM, (2) leaf temperature for understory leaves is equal to the ambient temperature and (3) leaf temperature for canopy leaves (under direct sunlight) is about 5 °C higher than understory leaves (Rey‐Sánchez et al . ; Slot & Winter ). In total, there are 140 data entries (102 for canopy leaves, 38 for understory leaves) from 105 species in our study (Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…A wide variety of trees (broadleaf and coniferous species, from subtropical through boreal biomes) were shown to converge on a common, integrated T leaf , suggesting that tree leaves, particularly in boreal latitudes, deviate substantially from air temperature when weighted for photosynthesis (Helliker and Richter 2008). Slot and Winter (2017) showed that a wide range of tropical tree and liana species, regardless of canopy position, have optimal temperatures for leaf photosynthesis around 30°C, with a high-temperature threshold around 35°C that was also seen in earlier work (Doughty and Goulden 2008). Linking thermal and photosynthetic measurements can offer important insight into how forests, and the diversity of trees within those forests, respond to episodic thermal extremes.…”
Section: Application 2: Understanding How Thermal Variations Influencmentioning
confidence: 99%
“…Examples include photosynthesis and respiration (Slot and Winter 2017), as well as biophysical attributes such as leaf-to-air vapor pressure deficit (VPD), which is critical for estimating evapotranspiration and its influence on biogeochemistry. Temperature is also a fundamental characteristic of climate.…”
Section: Introductionmentioning
confidence: 99%